A práxis pedagógica no Centro Estadual Integrado de Educação Rural : um estudo em Educação do Campo e Agricultura Familiar em Vila Pavão/ ES - Jesus, José Pacheco de (2012)
Analyzes the pedagogical praxis from Centro Estadual Integrado de Educação Rural from Vila Pavão - ES (CEIER/VP-ES) in their relation to the Family Farm (FF) and the prospect of Rural Education (RE). Contextualizes historically the creation and deployment of CEIER's in the northwest region of Espirito Santo in 1980. Investigates educational practice in CEIER / VP-ES and their relationship with the local rural communities. Describes (dis)continuities that emerge from the practices experienced in the context of social-educational CEIER / VP-ES. Dialogues with the philosophical thought of Gramsci's praxis grounded in humanistic theory of Marx, emphasized by the liberating ideas of Paulo Freire and theoretical Sánchez Vázquez (2011). Also uses the concepts of "Knowledge-doings" (TARDIF, 2010), Educação do Campo (ARROYO, 2006, 2010; Caldart, 2008, 2011; FERNANDES, 2008a; 2008b; FOERSTE, 2008; MOLINA, 2009), FF, market and Agroecology (WANDERLEY, 2009; WILKINSON, 2008; ALTIERI, 2008) as a way of questioning an educational practice, not summarized in space/time in school, but also comprehensive local context of its "rural world as living space" (WANDERLEY, 2009) and without dichotomize think-act, work, education, man-nature, urban-rural, and school-life. Proposes, through these conceptions, and intends to reflect on the "master craft" (ARROYO, 2004) in the exercise of their educational practice effected in the process of "learning / teaching" from "knowledge of experience made" of learners and in collective construction from "epistemological curiosity" (Freire, 2009a). Provokes reflections on human need to socialize knowledge, promote "partnerships" (FOERSTE, 2005), experience "experiences" (BENJAMIN, 1994; LARROSA, 2004) in the relationship "work-education" (Frigotto, 2002) in the face of challenges, man of the countryside and the city, by the "green revolution" (ALTIERI, 2008), as "guide pedagogical practice”. Uses qualitative research methodology with ethnographic approach (ANDREW, 2005), through documentary analysis, participant observations (BRANDÃO, 1999, 2003), interviews, questionnaires and insertions in the context of the studied object (Freire, 1981). It will draw on case studies in André (2008), for "participant observation and in-depth interviews [as] the most effective means for the researcher to move closer to the systems of representation, classification and organization of the universe studied [...]" , the opportunity to understand, reflect, conceive and recreate new space / time about the world in which we live. Believes that, given the data, the CEIER / VP-ES carries a historical identity, from its origin in 1980, very strong with rural man. Evidence that's institution an identity linked to the root of social movements and a striking feature of the notion of belonging from their first teachers, then reaffirmed by current resistance manifested through pedagogical practices of the projects promoted by current teachers, agroecological activities performed, the FF activities triggered by local farmers, as opposed to that ideology of the Green Revolution. Show, the group studied, stress, thoughts, challenges and opportunities experienced by CEIER's in the public schools, since their Pedagogical Proposals to consolidate data, which sometimes come close, sometimes deviate from the perspective of a JV. Opens perspectives for other academic studieses